Challenging Thyroid Cases in Clinical Practice - Saifuddin, M (Bangladesh Journal of Medicine, 2023)
Thyroid disorders are prevalent, and their manifestations are divergent and sometimes it is very challenging to diagnose and deal with some Thyroid cases in clinical practice. Here seven different challenging cases will be discussed that will help clinicians to diagnose and treat such cases in dayto- day clinical practice. First case enlightened us that Thyroid function should not be assessed in seriously ill patients unless there is a strong suspicion of thyroid dysfunction, since there are many other factors in acutely or chronically ill euthyroid patients that influence thyroid function tests. The second case taught us that there is assay interference with Biotin ingestion and patients taking Biotin should hold the supplement for two days prior to assessing thyroid function. Subacute thyroiditis is a self-limiting inflammatory condition of the thyroid gland and COVID-19 virus infection may be associated with subacute thyroiditis as a complication that may occur in patients without any previous thyroid disorder that is revealed in third case. In Secondary hypothyroidism/Hypopituitarism, TSH may be low, normal, or even slightly elevated due to inactive TSH isoform in blood. The fourth case shows us that only TSH testing in clinical practice leads to missing Secondary hypothyroidism/Hypopituitarism. Learning from fifth case is that during monitoring of thyrotoxic patients taking ATDs, serum TSH may remain suppressed for several months after starting therapy and it is therefore not a good parameter for monitoring therapy early during treatment, rather we should rely on FT4 and FT3. The sixth case enlightened us that in case of low TSH in early pregnancy, Gestational transient Thyrotoxicosis should be excluded which is commonly associated with hyperemesis gravidarum with no prior history of thyroid disease, no stigmata of Graves’ disease (Goiter, ophthalmopathy) and a self-limited mild disorder. In poorly compliant patients, there may be a combination of high FT4 and high TSH that is revealed in the seventh case. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 189